Composite negative electrode material, negative electrode plate and secondary battery
By adopting a composite negative electrode material with a multi-layer heterostructure and using a porous carbon structure to coat nanosilicon, the problems of silicon-based materials expansion and gas production in lithium-ion secondary batteries are solved, and the safety performance and service life of the battery are improved.
Patent Information
- Application Number
- CN202411958837.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-29
AI Technical Summary
In existing lithium-ion secondary batteries, silicon-based materials will cause electrode structure collapse and active material to peel off during charging and discharging, resulting in capacity attenuation, and a large amount of gas is generated, affecting the safety performance and service life of the battery.
A composite anode material with a multi-layer heterostructure, including nanosilicon as the core and a non-uniform porous carbon structure as the cladding layer, is formed by high-temperature carbonization after layer-by-layer assembly by MOFs to form a carbon-nitrogen bond structure to limit the expansion of the silicon-based material and reduce the gas production of the battery.
It effectively limits the expansion of silicon-based materials, stabilizes the SEI film structure, reduces the gas production of the battery, and improves the safety performance and service life of the battery.
Smart Images

Figure BDA0005216584460000131 
Figure BDA0005216584460000141 
Figure BDA0005216584460000142
Abstract
Description
Technical Field
[0001] The present invention relates to the field of secondary batteries, and in particular to a composite negative electrode material, a negative electrode sheet and a secondary battery. Background Art
[0002] At present, the negative electrode material of secondary batteries mainly uses traditional graphite materials. Silicon-based materials are gradually increasing their proportion in negative electrode materials due to their significant specific capacity advantages. In the actual storage and application of lithium-ion secondary batteries, due to the continuous side reactions between the electrolyte and the electrodes, a large amount of gas will accumulate inside the battery, causing the battery to swell and deform, and the battery capacity to decrease, which in turn affects the safety performance of lithium-ion secondary batteries and greatly shortens the service life of lithium-ion secondary batteries.
[0003] However, silicon will produce a large volume effect during the charge and discharge process, leading to the collapse of the electrode structure and the peeling of active materials, resulting in rapid capacity decay. In addition, the poor conductivity of silicon has seriously affected the large-scale application of silicon as a negative electrode material. The surface coating process is a simple and effective method to improve the performance of electrode materials, and is widely used in the research and development and preparation of various silicon-carbon negative electrode materials. Coating a layer of material that can conduct Li+ on the surface of nano-silicon particles can accelerate the embedding of Li+ and reduce the risk of Li+ precipitation at the negative electrode interface, but conventional amorphous carbon-coated silicon-carbon negative electrode materials cannot solve the problem of gas production by side reactions of the battery. During the storage and use of the battery, the oxidative decomposition of carbonate substances in the electrolyte on the surface of the positive electrode is the main reason for the gas production of the battery cell, among which CO2 is the main component of the gas production.
[0004] In view of this, there is an urgent need to develop a composite negative electrode material that can both limit the expansion of silicon-based materials and reduce battery gas production. Summary of the invention
[0005] The purpose of the present invention is to provide a composite negative electrode material to address the deficiencies of the prior art, which can both limit the expansion of silicon-based materials and reduce the gas production of the battery.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A composite negative electrode material is a multi-layer heterogeneous structure, comprising an inner core and a coating layer coated on the outer surface of the inner core, wherein the inner core is nano-silicon and the coating layer is a non-uniform porous carbon structure.
[0008] Preferably, the particle size of the composite negative electrode material is 1-2 μm, and the particle size of the nano-silicon is 20-300 nm;
[0009] And / or, the specific surface area of the composite negative electrode material is 135m 2 / g-180m 2 / g.
[0010] Preferably, the ratio of the coating layer thickness to the particle size of the core nano-silicon is (10-15):1.
[0011] Preferably, the nitrogen content W1 of the composite negative electrode material is 6-16%, and the silicon content W2 is 8-10%.
[0012] Preferably, the porous carbon structure is formed by assembling MOFs layer by layer and then carbonizing at high temperature, and includes a carbon-nitrogen bond structure, specifically amino nitrogen, pyridinic nitrogen, pyrrolic nitrogen and graphitic nitrogen.
[0013] Preferably, before the coating layer is carbonized: the outer layer is selected from zeolite imidazole MOFs, and the inner layer is selected from amino-modified MOFs.
[0014] Preferably, the outer layer is selected from ZIF-8 and ZIF-67, and the inner layer is selected from MIL-125-NH2.
[0015] Preferably, the composite negative electrode material is tested by XPS, and based on the peak area of the structure containing carbon-nitrogen bonds, the proportion of amino nitrogen is N1, the proportion of pyridine nitrogen is N2, the proportion of pyrrole nitrogen is N3, and the proportion of graphite nitrogen is N4;
[0016] Among them, N1, N2, N3 and N4 satisfy the following relationship: 90%≤(N1+N2+N3)<100%; 2≤N2 / N3≤4; 1≤N1 / (N2+N3)≤2; 0<N4≤10%.
[0017] Preferably, N1 is 45-60%, N2 is 20-40%, and N3 is 6-12%.
[0018] Preferably, the nitrogen content W1 in the composite negative electrode material is 6-16%, and the silicon content W2 is 8-10%.
[0019] In addition, the present invention also provides a method for preparing a composite negative electrode material, comprising the following steps:
[0020] Step S1, dissolving the ligand and the metal salt in an organic solution, and preparing MOFs after heating reaction;
[0021] Step S2, placing nano-silicon particles in a polyvinyl pyrrolidone solution for pretreatment, adding MOFs and an organic solution and stirring to obtain a Si@MOFs precursor;
[0022] Step S3, placing the Si@MOFs precursor in an inert atmosphere and sintering at high temperature to obtain the composite negative electrode material;
[0023] Wherein, in step S3, the sintering temperature is 600-700°C, and the sintering time is 2-3h.
[0024] Preferably, in step S1, the ligand is selected from at least one of 2-aminoterephthalic acid and 2-methylimidazole;
[0025] and / or, the metal salt is selected from at least one of isopropyl titanate, tetrabutyl titanate, cobalt nitrate, cobalt chloride, cobalt sulfate, zinc nitrate, zinc chloride and zinc sulfate;
[0026] and / or, the organic solvent is selected from at least one of DMF, DMA, DMSO, methanol and ethanol;
[0027] And / or, MOFs is selected from at least one of MIL-53-NH2, MIL-101-NH2, MIL-125-NH2, ZIF-67 and ZIF-8.
[0028] In addition, the present invention also provides a negative electrode sheet, comprising the above-mentioned composite negative electrode material.
[0029] In addition, the present invention also provides a secondary battery, including a battery cell formed by winding a negative electrode sheet, a positive electrode sheet and a separator, an electrolyte, and a shell that encapsulates the battery cell and the electrolyte, wherein the negative electrode sheet is the above-mentioned negative electrode sheet.
[0030] Compared with the prior art, the beneficial effect of the present invention is that the composite negative electrode material provided by the present invention can not only limit the expansion of silicon-based materials, but also has good gas storage capacity to avoid battery bulging. Among them, the porous carbon structure is formed by assembling MOFs layer by layer and then carbonizing at high temperature. The rigid carbon skeleton after carbonization of MOFs has sufficient cavity volume inside, which can effectively buffer the volume expansion of silicon nanoparticles and ensure the structural stability of the SEI film. In addition to preventing direct contact between silicon particles and electrolyte, the functional group -NH2 retained on the carbon layer skeleton can play a role in chemical adsorption. At the same time, the pyrrole nitrogen and pyridine nitrogen sites formed after carbonization can also cooperate with the amino group to play a certain adsorption role due to the presence of lone pairs of electrons, that is, by reacting with CO2 gas molecules to form a covalent compound R-NHCOO - Binding CO2 inside its pores effectively reduces gas production during battery use and storage. DETAILED DESCRIPTION
[0031] In order to make the technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] According to the first aspect of the present application, the present application provides a composite negative electrode material, which is a multilayer heterogeneous structure, including an inner core and a coating layer coated on the outer surface of the inner core, the inner core is nano-silicon, and the coating layer is a non-uniform porous carbon structure.
[0033] Among them, the porous carbon structure is formed by assembling MOFs layer by layer and then carbonizing them at high temperature. Compared with conventional silicon-carbon materials, this material has a richer carbon layer skeleton structure, which limits the expansion of silicon nanoparticles, ensures the stability of the SEI film, and reduces the system effect.
[0034] In some embodiments, the ratio of the coating layer thickness to the particle size of the core nano-silicon is (10-15):1, for example, it can be 10:1, 12:1, 14:1 or 15:1.
[0035] In some embodiments, the composite negative electrode material has a particle size of 1-2 μm, such as 1 μm, 1.5 μm or 2 μm; the nano silicon particle size is 20-300 nm, such as 20 mm, 50 mm, 100 mm, 120 mm, 150 mm, 180 mm, 200 mm, 250 mm or 300 mm;
[0036] And / or, the specific surface area of the composite negative electrode material is 135m 2 / g-180m 2 / g, for example, it can be 135m 2 / g, 150m 2 / g, 155m 2 / g, 160m 2 / g, 165m 2 / g, 170m 2 / g, 175m 2 / g or 180m 2 / g. As the particle size of nano silicon particles decreases, the stability of the material increases. The smaller the particle size, the smaller the internal stress accumulation of the expanded silicon particles, ensuring the overall integrity of the silicon-carbon composite material. However, when the nano silicon particle size is too small, the surface area increases, the surface energy of the nano particles increases, and the stability weakens, causing the electrolyte to decompose preferentially with the nano particles.
[0037] In some embodiments, the nitrogen content W1 in the composite negative electrode material is 6-16%, for example, 6%, 8%, 10%, 12%, 14% or 16%; the silicon content W2 is 8-10%, for example, 8%, 9% or 10%.
[0038] In some embodiments, the porous carbon structure is formed by assembling MOFs layer by layer and then carbonizing at high temperature, and includes a carbon-nitrogen bond structure, specifically amino nitrogen, pyridinic nitrogen, pyrrolic nitrogen and graphitic nitrogen.
[0039] In addition to preventing direct contact between silicon particles and the electrolyte, the functional group -NH2 retained on the carbon layer skeleton can play a role in chemical adsorption. At the same time, the pyrrolic nitrogen and pyridinic nitrogen sites formed after carbonization can also cooperate with the amino group to play a certain adsorption role due to the presence of lone pairs of electrons, that is, by reacting with CO2 gas molecules to form a covalent compound R-NHCOO - Binding CO2 inside its pores effectively reduces gas production during battery use and storage.
[0040] In some embodiments, before the coating layer is carbonized: the outer layer is selected from zeolite imidazole MOFs, and the inner layer is selected from amino-modified MOFs. The outer layer MOFs protect the inner layer groups while providing a porous structure, which is beneficial to alleviate the expansion of silicon particles and better interface bonding, and the inner layer amino-modified MOF provides amino groups to absorb CO2.
[0041] In some embodiments, the outer layer is selected from ZIF-8 and ZIF-67, and the inner layer is selected from MIL-125-NH2. Preferably, the outermost layer is selected from ZIF-8, the middle layer is selected from ZIF-67, and the innermost layer is selected from MIL-125-NH2.
[0042] Among them, during the carbonization and sintering process, the outer layer MOF must be sacrificed first so that NH2 can retain the effect as much as possible, so the innermost layer is MIL-125-NH2. ZIF-67 has better interface bonding with the innermost layer MIL-125-NH2, and because it matches the lattice of the outermost layer ZIF-8, it has better bonding and is suitable for use as an intermediate layer. ZIF-8, because it fits the lattice of ZIF-67, can grow better, and its thermal stability is significantly better than ZIF-67, so it is used as the outer layer. The amino groups of ZIF-8, ZIF-67's ligand 2-methylimidazole, and MIL-125-NH2's ligand terephthalic acid will form pyridine nitrogen, pyrrole nitrogen, and graphite nitrogen during the carbonization process as the MOF skeleton collapses.
[0043] In some embodiments, the composite negative electrode material is tested by XPS, and based on the peak area of the structure containing carbon-nitrogen bonds, the proportion of amino nitrogen is N1, the proportion of pyridine nitrogen is N2, the proportion of pyrrole nitrogen is N3, and the proportion of graphite nitrogen is N4;
[0044] Among them, N1, N2, N3 and N4 satisfy the following relationship: 90%≤(N1+N2+N3)<100%; 2≤N2 / N3≤4; 1≤N1 / (N2+N3)≤2; 0<N4≤10%.
[0045] Among them, the larger the proportion of the peak area of pyridinic nitrogen and graphitic nitrogen, the more amino groups and imidazole rings are converted after carbonization. The larger the proportion of the amino nitrogen XPS peak area, the more amino groups are retained in the material after carbonization, and the stronger the absorption capacity of carbon dioxide. Pyridinic nitrogen and pyrrolic nitrogen have electrocatalytic properties and can accelerate the transmission of lithium ions. The larger the peak area of pyridinic nitrogen and pyrrolic nitrogen, the better the lithium ion transmission performance, but the gas adsorption performance will decrease. Graphitic nitrogen has lone pair electrons that can improve the overall conductivity of the composite material. The larger the proportion of the graphitic nitrogen peak area, the better the conductivity of the material, but the gas adsorption performance will decrease.
[0046] In some embodiments, N1 is 45-60%, for example, it can be 45%, 50%, 55% or 60%; N2 is 20-40%, for example, it can be 20%, 25%, 30%, 35% or 40%; N3 is 6-12%, for example, it can be 6%, 7%, 8%, 9%, 10%, 11% or 12%.
[0047] In some embodiments, the nitrogen content W1 in the composite negative electrode material is 6-16%, for example, 6%, 8%, 10%, 12% or 16%; the silicon content W2 is 8-10%, for example, 8%, 9% or 10%. The element proportions W1 and W2 of nitrogen and silicon are negatively correlated. The greater the proportion of nitrogen, the more amino groups retained in the material after carbonization, and the stronger the absorption capacity of carbon dioxide.
[0048] According to a second aspect of the present application, the present application provides a method for preparing a composite negative electrode material, comprising the following steps:
[0049] Step S1, dissolving the ligand and the metal salt in an organic solution, and preparing MOFs after heating reaction;
[0050] Step S2, placing nano-silicon particles in a polyvinyl pyrrolidone solution for pretreatment, adding MOFs and an organic solution and stirring to obtain a Si@MOFs precursor;
[0051] Step S3, placing the Si@MOFs precursor in an inert atmosphere and sintering at high temperature to obtain the composite negative electrode material;
[0052] Wherein, in step S3, the sintering temperature is 600-700°C, for example, it can be 600°C, 620°C, 640°C, 660°C, 680°C or 700°C; the sintering time is 2-3h, for example, it can be 2h, 2.5h or 3h.
[0053] In some embodiments, in step S1, the ligand is selected from at least one of 2-aminoterephthalic acid and 2-methylimidazole;
[0054] and / or, the metal salt is selected from at least one of isopropyl titanate, tetrabutyl titanate, cobalt nitrate, cobalt chloride, cobalt sulfate, zinc nitrate, zinc chloride and zinc sulfate;
[0055] and / or, the organic solvent is selected from at least one of DMF, DMA, DMSO, methanol and ethanol;
[0056] And / or, MOFs is selected from at least one of MIL-53-NH2, MIL-101-NH2, MIL-125-NH2, ZIF-67 and ZIF-8.
[0057] According to a third aspect of the present application, the present application provides a negative electrode sheet comprising the above-mentioned composite negative electrode material.
[0058] According to the fourth aspect of the present application, the present application provides a secondary battery, including a battery cell formed by winding a negative electrode sheet, a positive electrode sheet and a separator, an electrolyte, and a shell that encapsulates the battery cell and the electrolyte, wherein the negative electrode sheet is the above-mentioned negative electrode sheet.
[0059] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material. The positive electrode active material may include but is not limited to a chemical formula such as Li a Ni x Co y M z O 2-b N b (wherein 0.95≤a≤1.2, x>0, y≥0, z≥0, and x+y+z=1, 0≤b≤1, M is selected from a combination of one or more of Mn and Al, and N is selected from a combination of one or more of F, P, and S) The positive electrode active material may also be, but is not limited to, LiCoO2, LiNiO2, LiVO2, LiCrO2, LiMn2O4, LiCoMnO4, Li2NiMn3O8, LiNi 0.5 Mn 1.5O4, LiCoPO4, LiMnPO4, LiFePO4, LiNiPO4, LiCoFSO4, CuS2, FeS2, MoS2, NiS, TiS2, etc. The positive active material may also be subjected to a modification treatment, and the method for modifying the positive active material should be known to those skilled in the art. For example, the positive active material may be modified by coating, doping, etc. The material used for the modification treatment may include but is not limited to a combination of one or more of Al, B, P, Zr, Si, Ti, Ge, Sn, Mg, Ce, W, etc. The positive current collector is usually a structure or part for collecting current, and the positive current collector may be various materials in the art suitable for use as a positive current collector for a secondary battery. For example, the positive current collector may include but is not limited to metal foil, etc., and more specifically may include but is not limited to aluminum foil, etc.
[0060] The secondary battery also includes an electrolyte, which includes an organic solvent, an electrolyte lithium salt and an additive. Among them, the electrolyte lithium salt can be LiPF6 and / or LiBOB used in high-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, and LiPF6 used in low-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, LiPF6, and LiTFSI used in anti-overcharge electrolytes; it can also be at least one of LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2. The organic solvent can be a cyclic carbonate, including PC and EC; it can also be a chain carbonate, including DFC, DMC, or EMC; it can also be a carboxylic acid ester, including MF, MA, EA, MP, etc. The additives include but are not limited to at least one of film-forming additives, conductive additives, flame retardant additives, anti-overcharge additives, additives for controlling the content of H2O and HF in the electrolyte, additives for improving low-temperature performance, and multifunctional additives.
[0061] In some embodiments, the shell is made of stainless steel or aluminum-plastic film. Preferably, the shell is made of aluminum-plastic film.
[0062] The present invention will be described in further detail below in conjunction with specific implementation modes, but the implementation modes of the present invention are not limited thereto.
[0063] Example 1
[0064] Preparation of composite negative electrode materials
[0065] Step S1, dissolving 2-aminoterephthalic acid and isopropyl titanate in a mixed solvent of DMF and methanol, and reacting at 150° C. for 24 h in a high-pressure reactor to obtain MIL-125-NH2 (the mass ratio of 2-aminoterephthalic acid, isopropyl titanate, DMF and methanol is: 10:5:188:16);
[0066] Step S2, after pre-treating the nano silicon particles in a polyvinyl pyrrolidone solution, dissolving cobalt nitrate hexahydrate (Co(NO3)2·6H2O) in a methanol solution, adding the nano silicon particles and stirring for 30 min to obtain a suspension A (the mass ratio of Co(NO3)2·6H2O to methanol is 1:134);
[0067] Disperse MIL-125-NH2 in methanol to obtain suspension B (the mass ratio of MIL-125-NH2 to methanol is 1:29); mix suspension A and suspension B, add 2-methylimidazole and stir at room temperature for 24 hours to obtain the product MIL-125-NH2@Si@ZIF-67; (the mass ratio of MIL-125-NH2, Co(NO3)2·6H2O, 2-methylimidazole and nano-silicon is 5:2:2:3);
[0068] Zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and 2-methylimidazole were dissolved in methanol and then added to MIL-125-NH2@Si@ZIF-67 to form suspension C (the mass ratio of Zn(NO3)2·6H2O, 2-methylimidazole, MIL-125-NH2@Si@ZIF-67, and methanol was 6:1:50:7.5), and the precursor MIL-125-NH2@Si@ZIF-67@ZIF-8 was obtained by stirring at room temperature for 24 hours.
[0069] Step S3, placing the MIL-125-NH2@Si@ZIF-67@ZIF-8 precursor in an inert atmosphere, and sintering at 700° C. for 2 h to obtain the composite negative electrode material.
[0070] Among them, the particle size of the nano silicon particles is 200nm, and the average particle size of the composite negative electrode material is 1μm.
[0071] Preparation of negative electrode
[0072] The composite negative electrode material, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) are fully stirred and mixed in a deionized water solvent system at a mass ratio of 96:1:1.5:1.5, and then coated on the negative electrode current collector Cu foil, and dried, cold pressed, and slit to obtain a negative electrode sheet.
[0073] Preparation of positive electrode
[0074] The positive electrode active material, conductive single-layer carbon nanotube, conductive acetylene black, and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in an N-methylpyrrolidone solvent system at a mass ratio of 96:0.5:1.5:2, and then coated on the positive electrode current collector Al foil, and dried, cold pressed, and slit to obtain a positive electrode sheet.
[0075] Preparation of isolation membrane
[0076] A polyethylene (PE) porous polymer film is used as the isolation membrane.
[0077] Preparation of electrolyte
[0078] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 20:30:20:28:2, mass ratio) in a mass ratio of 8:92 is used as the electrolyte of a lithium-ion secondary battery.
[0079] Preparation of batteries
[0080] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, the separator is placed between the positive electrode sheet and the negative electrode sheet to play a role of safety isolation, and then wound to obtain an electrode assembly. The electrode assembly is placed in a packaging shell, the electrolyte is injected and vacuum-sealed to obtain a battery.
[0081] Example 2
[0082] Different from Example 1, the particle size of nano-silicon in this example is 50 nm.
[0083] The rest is the same as Example 1 and will not be described again here.
[0084] Example 3
[0085] Different from Example 1, the particle size of nano-silicon in this example is 100 nm.
[0086] The rest is the same as Example 1 and will not be described again here.
[0087] Example 4
[0088] Different from Example 1, the particle size of nano silicon in this embodiment is 50 nm, the mass ratio of MIL-125-NH2, Co(NO3)2·6H2O, 2-methylimidazole and nano silicon in step 2 is 5:3:3:3, the mass ratio of Zn(NO3)2·6H2O, 2-methylimidazole, MIL-125-NH2@Si@ZIF-67 and methanol is 18:3:100:15, and the particle size of the composite negative electrode material is 1.5 μm.
[0089] The rest is the same as Example 1 and will not be described again here.
[0090] Example 5
[0091] Different from Example 1, the particle size of nano silicon in this embodiment is 50 nm, the mass ratio of MIL-125-NH2, Co(NO3)2·6H2O, 2-methylimidazole and nano silicon in step 2 is 5:4:4:3, the mass ratio of Zn(NO3)2·6H2O, 2-methylimidazole, MIL-125-NH2@Si@ZIF-67 and methanol is 12:1:50:7.5, the stirring time at room temperature is 36 h, and the particle size of the composite negative electrode material is 2 μm.
[0092] The rest is the same as Example 1 and will not be described again here.
[0093] Example 6
[0094] Different from Example 1, the sintering temperature in step S3 of this example is 600°C.
[0095] The rest is the same as Example 1 and will not be described again here.
[0096] Example 7
[0097] Different from Example 1, the sintering time in step S3 of this example is 3 hours.
[0098] The rest is the same as Example 1 and will not be described again here.
[0099] Comparative Example 1
[0100] Different from Example 1, the negative electrode material of this comparative example is artificial graphite.
[0101] The rest is the same as Example 1 and will not be described again here.
[0102] Comparative Example 2
[0103] Different from Comparative Example 1, the negative electrode material of this comparative example is a silicon / amorphous carbon composite material.
[0104] The rest is the same as Example 1 and will not be described again here.
[0105] Comparative Example 3
[0106] Different from Comparative Example 1, the particle size of the nano-silicon in this comparative example is 300 nm.
[0107] The rest is the same as Example 1 and will not be described again here.
[0108] Comparative Example 4
[0109] Different from Example 1, the particle size of the nano-silicon in this comparative example is 20 nm.
[0110] The rest is the same as Example 1 and will not be described again here.
[0111] Comparative Example 5
[0112] Different from Example 1, the preparation steps of the composite negative electrode material in this comparative example are:
[0113] Step S1, dissolving 2-aminoterephthalic acid and isopropyl titanate in a mixed solvent of DMF and methanol, and reacting at 150° C. for 24 h in a high-pressure reactor to obtain MIL-125-NH2 (the mass ratio of 2-aminoterephthalic acid, isopropyl titanate, DMF and methanol is: 10:5:188:16);
[0114] Step S2:
[0115] After pretreatment of the nano-silicon particles in a polyvinyl pyrrolidone solution, zinc nitrate hexahydrate (Zn(NO3)2·6H2O) was dissolved in a methanol solution and then the nano-silicon particles were added and stirred for 30 min to obtain a suspension A (the mass ratio of Zn(NO3)2·6H2O to methanol was 1:109).
[0116] Disperse MIL-125-NH2 in methanol to obtain suspension B (the mass ratio of MIL-125-NH2 to methanol is 1:29); mix suspension A and suspension B, add 2-methylimidazole and histidine, and stir at room temperature for 24 hours to obtain the product MIL-125-NH2@Si@ZIF-8; (the mass ratio of MIL-125-NH2, Zn(NO3)2·6H2O, 2-methylimidazole, histidine, and nano-silicon is 5:2:2:0.1:3);
[0117] Dissolve cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and 2-methylimidazole in methanol and add MIL-125-NH2@Si@ZIF-8 to form suspension C (the mass ratio of Zn(NO3)2·6H2O, 2-methylimidazole, MIL-125-NH2@Si@ZIF-8, and methanol is 6:1:50:10), and stir at room temperature for 24 hours to obtain the precursor MIL-125-NH2@Si@ZIF-8@ZIF-67.
[0118] Step S3, placing the MIL-125-NH2@Si@ZIF-8@ZIF-67 precursor in an inert atmosphere, and sintering at 700° C. for 2 h to obtain the composite negative electrode material.
[0119] The rest is the same as Example 1 and will not be described again here.
[0120] Comparative Example 6
[0121] Different from Example 1, the preparation steps of the composite negative electrode material in this comparative example do not include step S3.
[0122] The rest is the same as Example 1 and will not be described again here.
[0123] Comparative Example 7
[0124] Different from Example 1, the preparation steps of the composite negative electrode material in this comparative example are:
[0125] Step S1, dissolving 2-aminoterephthalic acid and isopropyl titanate in a mixed solvent of DMF and methanol, and reacting in a high-pressure reactor at 150° C. for 24 hours to obtain MIL-125-NH2;
[0126] Step S2: placing nano-silicon particles in a polyvinyl pyrrolidone solution for pretreatment, adding the solution to methanol, dispersing MIL-125-NH2 in the methanol, and stirring at room temperature for 24 hours to obtain a MIL-125-NH2@Si precursor;
[0127] Step S3, placing the MIL-125-NH2@Si precursor in an inert atmosphere, and sintering it at 700° C. for 2 h to obtain the composite negative electrode material.
[0128] The rest is the same as Example 1 and will not be described again here.
[0129] Comparative Example 8
[0130] Different from Example 1, the preparation steps of the composite negative electrode material in this comparative example are:
[0131] Step S1, dissolving 2-aminoterephthalic acid and isopropyl titanate in a mixed solvent of DMF and methanol, and reacting in a high-pressure reactor at 150° C. for 24 hours to obtain MIL-125-NH2;
[0132] Step S2: After pre-treating the nano-silicon particles in a polyvinyl pyrrolidone solution, dissolving cobalt nitrate hexahydrate (Co(NO3)2·6H2O) in a methanol solution, adding the nano-silicon particles and stirring for 30 min to obtain a suspension A; dispersing MIL-125-NH2 in methanol to obtain a suspension B (the mass ratio of MIL-125-NH2 to methanol is 1:29); mixing the suspension A and the suspension B, adding 2-methylimidazole and stirring at room temperature for 24 h to obtain a MIL-125-NH2@Si@ZIF-67 precursor;
[0133] Step S3, placing the MIL-125-NH2@Si@ZIF-67 precursor in an inert atmosphere, and sintering at 700° C. for 2 h to obtain the composite negative electrode material.
[0134] The rest is the same as Example 1 and will not be described again here.
[0135] Performance Testing
[0136] The obtained materials were subjected to the following tests.
[0137] (1) XPS test: By integrating and calculating the peak area of each element in the XPS spectrum of the composite negative electrode material, the content of different elements in the samples coated with silicon particles of different particle sizes is confirmed, and the number of amino groups in the coating shell layer between different samples is further calculated.
[0138] (2) Specific surface area test: The composite negative electrode material was placed in a vacuum environment at 100°C for degassing for 2 hours, and then nitrogen was introduced to adsorb nitrogen in a liquid nitrogen temperature environment until saturation. The Brunauer–Emmett–Teller (BET) model was then used to calculate and analyze the specific surface area, and the Barrett–Joyner–Halenda (BJH) model was used to analyze the material pore volume and pore size distribution information.
[0139] (3) Gas expansion rate test: adjust the battery power to the same SOC state and record its initial volume, place it in a constant temperature oven at 60°C, take it out every 5 days and cool it to room temperature, measure and record its volume change by water displacement method, then put it back into the constant temperature oven and store it until the target time or the battery shows obvious swelling, then stop storage and testing. Water displacement method volume measurement: use a balance to weigh the mass m of the sample (battery or positive and negative electrode monopole) to be measured; then completely immerse the test sample in a container filled with water, while ensuring that it does not touch the bottom or the wall, place a tensile gauge above the water container, record the tensile gauge reading F after the sample is completely immersed in water, and use the formula ρVg=mg-F to calculate the total volume V of the test sample, and then obtain the expansion rate of the battery.
[0140] The test results are shown in Table 1-2 below.
[0141] Table 1
[0142]
[0143]
[0144] Table 2
[0145]
[0146] From the data comparison of Examples 1-7 and Comparative Examples 1-8 in Table 1-2, it can be seen that the gas production expansion rate of the battery of the composite negative electrode material provided in the present application is much smaller than that of the battery using conventional negative electrode active materials, and the difference in gas production expansion rate can be up to 3 times or more. This shows that the silicon-carbon negative electrode material provided by the present invention can well capture and adsorb a part of the CO2 gas produced by the side reaction, has good gas storage capacity, and greatly improves the high-temperature storage safety performance of the battery cell.
[0147] From the data comparison of Examples 1-5 and Comparative Examples 3-4, it can be seen that as the particle size of the coated silicon particles continues to decrease, the N element content in the silicon-carbon material of equal mass is higher, the corresponding material retains more amino groups, and the adsorption capacity for CO2 is also stronger. When the nano-silicon particle size is too large, the larger silicon particles have greater expansion stress, and there is a situation where the silicon particles are fully embedded with lithium and expand to expose the coating layer. The exposed silicon particles are in direct contact with the electrolyte, which will cause the decomposition reaction of the electrolyte to intensify and increase the gas production. When the nano-silicon particle size is too small, although the amino group content inside the composite negative electrode material of equal mass is higher, the small-diameter nano-silicon particles will be filled into the pores of the carbonized skeleton, resulting in blockage of the pores inside the carbonized skeleton, reducing the specific surface area of the material and reducing the adsorption capacity for CO2.
[0148] It can be seen from the data comparison of Example 1 and Comparative Examples 6-8 that when there is no ZIF-8 in the outermost layer, since the thermal stability of ZIF-8 is higher than that of ZIF-67, the degree of skeleton collapse after the overall carbonization of the material is higher, resulting in a decrease in specific surface area, and more -NH2 in the inner layer is converted into pyrrole nitrogen and pyridine nitrogen, and the adsorption capacity of CO2 becomes weaker. When ZIF-67 is placed in the outermost layer and its skeleton is carbonized, it is easy to collapse and cause a decrease in surface area, and the ZIF-8 pore size is larger than ZIF-67, and the overall specific surface area of the material becomes smaller after being placed in the middle layer, affecting adsorption performance. When the MOFs layer is not carbonized, it will cause the specific surface area to be greatly increased, and the gas adsorption performance is better, but the material resistance is greatly increased, thereby increasing the internal resistance of the battery.
[0149] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A composite negative electrode material, characterized in that: The composite negative electrode material is a multi-layer heterogeneous structure, including a core and a coating layer coated on the outer surface of the core, the core is nano-silicon, and the coating layer is a non-uniform porous carbon structure.
2. The composite negative electrode material according to claim 1, characterized in that: The particle size of the composite negative electrode material is 1-2 μm, and the particle size of the nano-silicon is 20-300 nm; And / or, the specific surface area of the composite negative electrode material is 135m 2 / g-180m 2 / g.
3. The composite negative electrode material according to claim 1, characterized in that: The ratio of the coating layer thickness to the particle size of the inner core nano-silicon is (10-15):
1.
4. The composite negative electrode material according to claim 1, characterized in that The nitrogen content W1 of the composite negative electrode material is 6-16%, and the silicon content W2 is 8-10%.
5. The composite negative electrode material according to claim 1, characterized in that: The porous carbon structure is formed by assembling MOFs layer by layer and then carbonizing at high temperature, and includes a carbon-nitrogen bond structure, specifically amino nitrogen, pyridinic nitrogen, pyrrolic nitrogen and graphitic nitrogen.
6. The composite negative electrode material according to claim 1, characterized in that: Before the coating layer is carbonized: the outer layer is selected from zeolite imidazole MOF, and the inner layer is selected from amino-modified MOF; And / or, the outer layer is selected from at least one of ZIF-8 and ZIF-67, and the inner layer is selected from MIL-125-NH 2、 At least one of MIL-53-NH2 and MIL-101-NH2.
7. The composite negative electrode material according to claim 1, characterized in that: The composite negative electrode material is tested by XPS. Based on the peak area of the structure containing carbon-nitrogen bonds, the proportion of amino nitrogen is N1, the proportion of pyridine nitrogen is N2, the proportion of pyrrole nitrogen is N3, and the proportion of graphite nitrogen is N4; Among them, N1, N2, N3 and N4 satisfy the following relationship: 90%≤(N1+N2+N3)<100%; 2≤N2 / N3≤4; 1≤N1 / (N2+N3)≤2; 0<N4≤10%.
8. The composite negative electrode material according to claim 7, characterized in that: The N1 is 45-60%, the N2 is 20-40%, and the N3 is 6-12%.
9. A negative electrode sheet, characterized in that: The composite negative electrode material comprises the composite negative electrode material according to any one of claims 1 to 8.
10. A secondary battery, characterized in that: Including the negative electrode sheet as claimed in claim 9.
Citation Information
Patent Citations
Preparation method of silicon-carbon composite material
CN109742355A
Fully enclosed metal-carbon-dioxide battery and preparation method thereof
CN110112512A
Lithium ion battery negative electrode material and preparation method thereof
CN114824228A
Low-expansion silicon-based composite negative electrode material, preparation method thereof and lithium ion battery
CN115020710A
Negative electrode material, negative electrode plate and battery
CN115663154A